Local probes show that framework modification in zeolites occurs on ammonium exchange without calcination - Sartbaeva, A; Rees, N; Edwards, P; Ramirez-Cuesta, A; Barney, E (2013)
Framework modification involving a change in the Al environment from tetrahedral to octahedral is frequently reported in ammonium-exchanged zeolites after calcination, steaming, acid wash and other harsh treatments. We characterized Na-Y and partially exchanged NH4-Y zeolites by spectroscopic and diffraction methods in order to determine if NH4 exchange itself causes framework modification. High-resolution MAS SS NMR data show that even without calcination, some Al atoms change their local environment from tetrahedral to octahedral. PDF analysis corroborates this change and shows an increase in the aluminium coordination number. TEM images show no significant change in morphology of the crystallites, and no major changes in crystallinity are detected by X-ray diffraction. A similar result is obtained on Na-A zeolite suggesting that such increase in the coordination number of Al atoms during the exchange is a common feature in zeolites. Local probes, NMR and PDF analysis show changes in the local environments of Al atoms in the framework, which are usually not possible to see in the average structure. This journal is © The Royal Society of Chemistry 2013.